KABUT PERANG ASIMETRIS: KOMPLEKSITAS PENEGAKAN HUKUM HUMANITER DALAM KONFLIK MODERN - Pio Lohitniate Nainggolan; Erfan Indra Darmawan, Tarsisius Susilo, Rapi Tadung , Andar Dodianto Panggabean (JOURNAL OF LAW AND NATION, 2025)
Contemporary armed conflicts are characterized by asymmetric and hybrid features, such as proxy warfare, cyber operations, urban warfare, and digital propaganda. These conditions pose significant challenges to the enforcement of International Humanitarian Law (IHL), both globally and in Indonesia’s national context. This paper analyzes how these modern aspects blur the lines of the law of war and weaken reciprocity mechanisms, and examines Indonesia’s strategic adaptation needed to uphold IHL while maintaining state sovereignty and security. Using a normative qualitative approach with literature review and case analysis, the study compares international cases (Ukraine, Gaza, Syria) and national cases (Papua) to understand these phenomena. The findings indicate that the dynamics of modern weaponry and unconventional tactics put great pressure on fundamental IHL principles but also open space for defense policy innovation and international cooperation. By combining adherence to humanitarian norms with military effectiveness, Indonesia must enhance IHL training for its troops, refine its national legal framework, and strengthen humanitarian diplomacy and multi-stakeholder coordination. The contribution of this study is in presenting the perspective of an Indonesian military officer who integrates national security interests with humanitarian norms in a novel way to protect the populace and uphold the unitary state.